Development of a Questionnaire Evaluating the Knowledge, Attitude, and Practice on Geriatric Dermatology among Elderly Caregivers - Shannaz Nadia Yusharyahya; Valdi Ven Japranata; Christine Lieana; Lili Legiawati; Rinadewi Astriningrum; Wresti Indriatmi (eJournal Kedokteran Indonesia, 2022)
Information concerning the extent of knowledge, attitude, and practice of elderly caregivers about dermatological care are still limited. This present study aimed to develop a tool with decent validity and reliability to delineate such profiles. A questionnaire was designed by geriatric dermatology experts, followed by content validation and reliability tests using Aiken’s V coefficient, Kuder-Richardson Formula 20 (KR-20) or Cronbach’s α, and Pearson’s correlation. The developed instrument was tested on elderly caregivers, before and after education. Obtained data were analyzed using appropriate inferential statistics. We found that the Aiken’s V coefficient for each item was ≥0.70; KR-20 in knowledge section was 0.81; Cronbach’s α in attitude and practice section were 0.81 and 0.80, respectively; and Pearson’s correlation in all sections was above 0.80. Significant disparities were observed in the initial knowledge (p=0.005) and attitude (p=0.020) based on academic levels. In addition, overall scores generally increased upon education (p<0.001). Therefore, the questionnaire is valid and reliable for assessing elderly caregivers' competencies in geriatric dermatology of which could be improved by education.